كفاية راس مال المصارف وفق متطلبات بازل 3 دراسة تقييمية لمصرف الخليج التجاري كحالة دراسية - قرداغي, أ.د. كاوه‌ محمد فرج; جلال, طالبة الماجستير: مريم على (Sulaimani Journal for Humanities, 2023)
Capital adequacy is of great importance in the banking system in light of the global regulatory, changes of recent years with the increase in risks and the multiplicity of financial crises, as the global control systems have imposed special standards, carried out by the International Basel Committee in order to enhance the capacity of capital in order to reach a more flexible and stable banking system. Therefore, the adequacy of banking capital leads to activating and improving the efficiency of the financial performance of banks, as the study seeks to explain the behavior of the phenomenon referred to in order to protect depositors. This study seeks to shed light on its variables represented by the adequacy of banking capital and the Basel 3 standard to show the extent of the commitment of commercial banks in Iraq in general and the Gulf Commercial Bank in particular. The study reached a number of conclusions, the most important of which is that the mentioned bank exceeded the rate applied by Basel 3 10%, which reflects the state of weakness in the field of the bank’s investment of its assets on the one hand, and the bank’s ability to fulfill its obligations on the other hand.
Keywords: key words Banking capital adequacy; Basel III committee standards; credit; market and operational risks